Adjuvant therapy following neoadjuvant chemotherapy and surgery for oesophageal adenocarcinoma in patients with clear resection margins. (4th May 2021) - Bott, Rebecca K.; Beckmann, Kerri; Zylstra, Janine; Wilkinson, Michelle J.; Knight, William R. C.; Baker, Cara R.; Kelly, Mark; Maisey, Nick; Waters, Justin; Van Hemelrijck, Mieke; Smyth, Elizabeth C.; Allum, William H.; et al.
Abstract: Background: The role of adjuvant therapy in patients with oesophagogastric adenocarcinoma treated by neoadjuvant chemotherapy (NAC) and surgery is contentious. In UK practice, surgical resection margin status is often used to classify patients into receiving adjuvant treatment. This study aimed to assess any survival benefit of adjuvant therapy in patients with clear resection margins. Methods: This was a retrospective collaborative cohort study combining two prospectively collected UK institutional databases of patients with oesophageal adenocarcinoma. Multivariable Cox regression and propensity matched analyses were used to compare overall and recurrence-free survival according to the adjuvant treatment. Results: Of 374 patients with clear resection margins, 221 patients (59%) had no adjuvant treatment, 137 patients (37%) had adjuvant chemotherapy and 16 patients (4%) had adjuvant chemoradiotherapy. For patients who had received NAC (290, 76%), when adjuvant chemotherapy was compared to no adjuvant treatment, hazard ratios (HRs) favoured adjuvant chemotherapy but did not reach independent significance (overall survival [OS] HR 0.65 95% confidence interval [CI] 0.40–1.06; p  .0.087). Responders to NAC (Mandard 1–3) were seemingly more likely to demonstrate a survival benefit from adjuvant chemotherapy (HR 0.42 95% CI 0.15–1.11; p  .1.081). Conclusions: Although no independent survival benefit was observed, the point estimates favoured adjuvant treatment, predominantly in patients with chemo-responsive tumours.